Capture point-based controller using real-time zero moment point manipulation for stable bipedal walking in human environment - Hong, Young Dae (Sensors (Switzerland), 2019)
For collaboration of humans and bipedal robots in human environments, this paper proposes a stability control method for dynamically modifiable bipedal walking using a capture point (CP) tracking controller. A reasonable reference CP trajectory for the CP tracking control is generated using the real-time zero moment point (ZMP) manipulation without information on future footstep commands. This trajectory can be modified at any time during the single support phase according to a given footstep command. Accordingly, this makes it possible for the robot to walk stably with dynamically modifiable walking patterns, including sudden changes in navigational commands during the single support phase. A reference CP trajectory during the double support phase is also generated for continuity. The CP of the robot is controlled to track the reference trajectory using a ZMP-based CP tracking controller. The ZMP while walking is measured by the force-sensing resistor sensors mounted on the sole of each foot. A handling method for infeasible footstep commands is utilized so that the manipulated ZMP satisfies the allowable ZMP region for stability. The validity of the proposed method is verified through simulations and experiments.
Keywords: Capture point (CP); Inverted pendulum model; Walking pattern; Walking stability; Zero moment point; Algorithms; Biomechanical Phenomena; Computer Simulation; Humans; Robotics; Walking; 3-D linear inverted pendulum model (LIPM); Capture point (CP); Modifiable walking pattern; Walking stability control; Zero moment point (ZMP) manipulation